‘Jamming’ With the Computer: Artificial Intelligence and Jazz Music Education - Bert Johnson (Journal of the Association for Technology in Music Instruction, 2025)
This article provides a preliminary discussion on the evolution of jazz music play-alongs in the individual practice of time feel. Within the history of jazz pedagogy, play-alongs have been a continual tool for learning repertoire and honing in on one’s ability to play with a harmonic and rhythmic vocabulary suitable to a variety of jazz genres such as swing, straight-feel and bossa nova. Due to the advancements in artificial intelligence and software development, new tools for individual music practice have emerged in the form of apps for computer and mobile devices. Apps such as iReal Pro (iRP) and Genius Jamtracks (GJT) demonstrate artificial intelligence technology that allows musicians to practice with accompaniment that has variable rhythmic and harmonic features mimicking the unpredictability that occurs in live performance. The article closes with a discussion on the potential uses these technological advancements have within jazz music education at a variety of age levels and settings.
Keywords: artificial intelligence; jazz music education; play-along apps